Annotation and characterization of the Plasmodium vivax rhoptry neck protein 4 (PvRON4) (2013)
Background: The tight junction (TJ) is one of the most important structures established during merozoite invasion of host cells and a large amount of proteins stored in Toxoplasma and Plasmodium parasites’ apical organelles are involved in forming the TJ. Plasmodium falciparum and Toxoplasma gondii apical membrane antigen 1 (AMA-1) and rhoptry neck proteins (RONs) are the two main TJ components. It has been shown that RON4 plays an essential role during merozoite and sporozoite invasion to target cells. This study has focused on characterizing a novel Plasmodium vivax rhoptry protein, RON4, which is homologous to PfRON4 and PkRON4. Methods: The ron4 gene was re-annotated in the P. vivax genome using various bioinformatics tools and taking PfRON4 and PkRON4 amino acid sequences as templates. Gene synteny, as well as identity and similarity values between open reading frames (ORFs) belonging to the three species were assessed. The gene transcription of pvron4, and the expression and localization of the encoded protein were also determined in the VCG-1 strain by molecular and immunological studies. Nucleotide and amino acid sequences obtained for pvron4 in VCG-1 were compared to those from strains coming from different geographical areas. Results: PvRON4 is a 733 amino acid long protein, which is encoded by three exons, having similar transcription and translation patterns to those reported for its homologue, PfRON4. Sequencing PvRON4 from the VCG-1 strain and comparing it to P. vivax strains from different geographical locations has shown two conserved regions separated by a low complexity variable region, possibly acting as a “smokescreen”. PvRON4 contains a predicted signal sequence, a coiled-coil α-helical motif, two tandem repeats and six conserved cysteines towards the carboxyterminus and is a soluble protein lacking predicted transmembranal domains or a GPI anchor. Indirect immunofluorescence assays have shown that PvRON4 is expressed at the apical end of schizonts and co-localizes at the rhoptry neck with PvRON2.